2017
DOI: 10.3389/fnmol.2017.00386
|View full text |Cite
|
Sign up to set email alerts
|

The Enigmatic Role of GBA2 in Controlling Locomotor Function

Abstract: The non-lysosomal glucosylceramidase GBA2 catalyzes the hydrolysis of glucosylceramide to glucose and ceramide. Loss of GBA2 function results in accumulation of glucosylceramide. Mutations in the human GBA2 gene have been associated with hereditary spastic paraplegia (HSP) and autosomal-recessive cerebellar ataxia (ARCA). Patients suffering from these disorders exhibit impaired locomotion and neurological abnormalities. GBA2 mutations found in these patients have been proposed to impair GBA2 function. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 58 publications
0
23
0
Order By: Relevance
“…Ceramides are further deacetylated to sphingosines that can be broken down or recycled for sphingolipid synthesis by the salvage pathway [25]. Non-lysosomal pathways of degradation also exist and for instance glucosylceramides can be degraded not only by the lysosomal glucocerebrosidase, but also by the non-lysosomal glucocerebrosidase (encoded by the GBA2 gene) and the cytosolic Klothorelated glucocerebrosidase (encoded by the GBA3 gene) [26][27][28][29][30][31]. Fig.…”
Section: Metabolism Of Glycosphingolipidsmentioning
confidence: 99%
“…Ceramides are further deacetylated to sphingosines that can be broken down or recycled for sphingolipid synthesis by the salvage pathway [25]. Non-lysosomal pathways of degradation also exist and for instance glucosylceramides can be degraded not only by the lysosomal glucocerebrosidase, but also by the non-lysosomal glucocerebrosidase (encoded by the GBA2 gene) and the cytosolic Klothorelated glucocerebrosidase (encoded by the GBA3 gene) [26][27][28][29][30][31]. Fig.…”
Section: Metabolism Of Glycosphingolipidsmentioning
confidence: 99%
“…The mutations found in the GBA2 gene are either missense mutations, exchanging one amino acid for another, or nonsense mutations, leading to a premature transcriptional stop and thereby protein truncation (17). Most of the missense mutations are located in the C-terminal catalytic domain, and those leading to protein truncation lack the catalytic domain (17). The majority of SPG46 patients carry homozygous mutations and only a few are compound heterozygous mutant carriers (Table 1) (17).…”
mentioning
confidence: 99%
“…Most of the missense mutations are located in the C-terminal catalytic domain, and those leading to protein truncation lack the catalytic domain (17). The majority of SPG46 patients carry homozygous mutations and only a few are compound heterozygous mutant carriers (Table 1) (17). Some of the mutations have been analyzed in vitro and failed to produce a ␤-glucosidase activity (18).…”
mentioning
confidence: 99%
“…Altogether, targeting GBA2 does not have the same consequences in humans as in mice; humans depend to a much greater extent on GBA2 for proper development of the central nervous system and motor control in arms and legs. This species difference is not understood at present [29]. Further, it may appear paradoxical that, in humans, different ways of targeting GBA2 have different consequences, as the GBA2 inhibitor miglustat is well tolerated while mutations in the GBA2 gene result in a range of neurological and non-neurological symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…The genetic abnormalities identified in the human GBA2 gene include missense, nonsense, splice site, and frameshift mutations ( Fig 1A), most of which are present in a homozygous fashion. It is unclear how the mutations in the GBA2 gene give rise to the range of disease manifestations seen in SPG46 and MSS patients [29]. To obtain insights into the physiological role of GBA2 and into the etiology of SPG46 and MSS, we previously modeled ten SPG46-associated GBA2 mutations in the cDNA coding for human GBA2, and found that single amino acid-substituted and C-terminally truncated forms of GBA2 failed to cleave its substrate [22].…”
Section: Introductionmentioning
confidence: 99%